2014
DOI: 10.1002/jts.21921
|View full text |Cite
|
Sign up to set email alerts
|

Verbal Learning Deficits in Posttraumatic Stress Disorder and Depression

Abstract: Verbal learning and memory deficits are frequently reported in posttraumatic stress disorder (PTSD), but may be a product of its psychiatric comorbidities, especially major depressive disorder (MDD). To evaluate this hypothesis, 25 medication-free patients with PTSD and comorbid MDD were compared to 148 medication-free patients with equally severe MDD alone and to 96 nonpatients on a measure of verbal learning and memory. Additional measures of attention, working memory, and executive function were administere… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
7
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 61 publications
1
7
1
Order By: Relevance
“…This finding is inconsistent with previous episodic memory research that has demonstrated that episodic memory deficits associated with PTSD are more pronounced for verbal compared to visual memory (Brewin et al, 2007). However, they align with previous studies demonstrating impaired visual WM in PTSD (Olff et al, 2014), but contradict studies that have reported impaired verbal WM (e.g., El-Hage et al, 2006;Tian et al, 2014;Stricker et al, 2015) or no association between verbal and visual WM and PTSD (e.g., Scheiner et al, 2014;Wrocklage et al, 2016). In the present study, whereby the visual and verbal material were carefully matched regarding the structure and format of the stimuli and assessed within the same paradigm (Swick et al, 2017), it seems that visual WM was impaired.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…This finding is inconsistent with previous episodic memory research that has demonstrated that episodic memory deficits associated with PTSD are more pronounced for verbal compared to visual memory (Brewin et al, 2007). However, they align with previous studies demonstrating impaired visual WM in PTSD (Olff et al, 2014), but contradict studies that have reported impaired verbal WM (e.g., El-Hage et al, 2006;Tian et al, 2014;Stricker et al, 2015) or no association between verbal and visual WM and PTSD (e.g., Scheiner et al, 2014;Wrocklage et al, 2016). In the present study, whereby the visual and verbal material were carefully matched regarding the structure and format of the stimuli and assessed within the same paradigm (Swick et al, 2017), it seems that visual WM was impaired.…”
Section: Discussioncontrasting
confidence: 99%
“…Some findings have revealed impaired visual WM in PTSD patients compared to trauma-exposed matched controls (e.g., Olff et al, 2014), whereas other studies have reported impaired verbal WM, typically measured using digit span, in trauma-exposed patients, particularly those with PTSD, compared to trauma survivors without PTSD and healthy non-trauma-exposed controls (e.g., El-Hage et al, 2006;Stricker et al, 2015;Tian et al, 2014). However, other researchers have found that verbal (e.g., Scheiner et al, 2014;Wrocklage et al, 2016) and visual (Neylan et al, 2004) WM deficits were not associated with PTSD. It is important to note that the verbal and visual WM tests employed in these studies were not carefully matched regarding the structure and format of the stimuli (Swick et al, 2017).…”
mentioning
confidence: 97%
“…Verbal WM is more commonly examined, typically using standardized tests such as digit span. Findings here are mixed, with impaired (Jenkins et al, 2000; Gilbertson et al, 2001; Vasterling et al, 2002; El-Hage et al, 2006; Tian et al, 2014; Stricker et al, 2015) and intact (Uddo et al, 1993; Zalewski et al, 1994; Neylan et al, 2004; Moores et al, 2008; Scheiner et al, 2014; Wrocklage et al, 2016) performance both reported.…”
Section: Introductionmentioning
confidence: 68%
“…Deficits in episodic memory have been most often observed using standardized measures to assess list learning and recall (Bremner et al, 1993; Yehuda et al, 1995; Scheiner et al, 2014). One review suggested that verbal memory is consistently impaired in PTSD (Johnsen & Asbjørnsen, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Scheiner et al. (2014) reported that participants with PTSD and comorbid MDD performed comparably with all the groups and within the normal functioning range on measures of attention. Memory deficits have consistently been reported for both PTSD and MDD, individually (Lim et al., 2013; McIntyre et al., 2013; Rock et al., 2014; Scott et al., 2015).…”
Section: Introductionmentioning
confidence: 99%